Temporo-spatial gait parameters during street crossing conditions: a comparison between younger and older adults - Vieira, Edgar R.; Lim, Hyun-Hwa; Brunt, Denis; Hallal, Camilla Z.; Kinsey, Laura; Errington, Lisa; Gonçalves, Mauro [UNESP] (Elsevier B.V., 2015)
Most traffic accidents involving pedestrians happen during street crossing. Safe street crossing by older adults requires complex planning and imposes high cognitive demands. Understanding how street crossing situations affect younger and older adults'gait is important to create evidence-based policies, education and training. The objective of this study was to develop and test a method to evaluate temporo-spatial gait parameters of younger and older adults during simulated street crossing situations. Twenty-two younger (25 +/- 2 years old) and 22 older adults (73 +/- 6 years old) who lived independently in the community completed 3 walking trials at preferred gait speed and during simulated street crossing with regular and with reduced time. There were significant differences between groups (p < 0.001) and conditions (p < 0.001). Older adults'street crossing walking speed was higher than their preferred speed (p < 0.001). Gait during simulated street crossing resulted in significant and progressive gait changes. The methods developed and tested can be used to (1) evaluate if people are at risk of falls and accidents during street crossing situations, (2) to compare among different groups, and (3) to help establish appropriate times for older pedestrians to cross streets safely. The current time to cross streets is too short even for healthy older adults. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Gait; Street crossing; Dual-task; Older adults; Temporo-spatial parameters